The impact of high intensity interval training (HIIT) on the performance of elite rowing athletes - Butt, M. R.; Butt, M. G.; Anjum, G. S. (Journal of Educational Research and Social Sciences Review, 2023)
Background: The rowing being the fitness sports mainly depends upon the endurance component of fitness as valued by the trainers and coaches. But examination of latest training methods to attain optimal performance from elite rowing athletes compelled the trainers to develop combination of cross-fitness and high intensity training versions to achieve competitive performances.